Crisis as opportunity—manifestations of civic practice in Libyan governance and rule of law - Brinkman, Anne-Marie (Frontiers in Political Science, 2025)
In Libya’s protracted conflict, authoritarian, illiberal, and democratic practises exist at local and (inter)national levels. The repeated occurrence of crises in governance and rule of law, such as sudden restrictions on civil society or deferred elections, opens a window for the emergence of civic practice. Drawing on Kaldor’s concept of war and peace logic and a development ethics viewpoint, this study will critically discuss how manifestations of civic logic depend to start with on inclusive actor selection. This paper, based on Libyan-led co-inquiries and an analysis of dialogues and actions from an EU-funded rule of law programme, will demonstrate how the involvement of a diverse group of Libyans initiates manifestations of civic practice that are used during times of crisis.